Awareness of health care staff regarding indicated and contraindicated medication during pregnancy at Kirkuk city hospitals - Darya Yaseen Mustafa; DhiaaAlrahman H. Abdullah (College of Nursing,University of Mosul, 2019)
Background: pregnant women may need medication to manage some of problems occurring during pregnancy. Some of medication considered safe and other unsafe, medical and nursing staff should aware of safe and unsafe medication to prevent further damage to the pregnant women. Objectives: to assess healthcare worker awareness regarding indicated and contraindicated medication during pregnancy at Kirkuk city hospitals. Methodology: A quantitative design using descriptive study was carried out at Kirkuk city hospitals from 1st of October, 2017, up to the 1st of October, 2018. A non-probability (purposive) sample of (86) staff working in maternity units was used. A constructed questionnaire was used for the purpose of the study which consisted of two parts: the demographic data of the sample, andthe awareness of healthcare worker regarding indicated and contraindicated medication during pregnancy. The data were collected through the use of self-administration techniques they were analyzed through the application of descriptive statistical analysis and inferential statistical data analysis. Results: The findings of the study indicated that (60.5%) of the samples were working in Kirkuk general hospital, (55.8%) were between age group (20-29 years), (57%) of the sample were nurses, (53.5%) of them were having 1-5 years of experience, and (58.1%) do not training in medication session. Conclusions: most healthcare worker unaware of indicated and contraindicated medication during pregnancy. Keys; awareness, indicated medication, contraindicated medication, pregnancy.